Republic of Korea Financial Sector Assessment Program : Detailed Assessment of Observance - Basel Core Principles folr Effective Banking Supervision - International Monetary Fund (World Bank, Washington, DC, 2014)
This assessment of the current state of the implementation of the Basel core principles for effective banking supervision (BCP) in the Republic of Korea has been completed as part of a financial sector assessment program (FSAP) update undertaken by the international monetary fund (IMF) and the World Bank (WB) during 2013. It reflects the regulatory and supervisory framework in place as of the date of the completion of the assessment. An assessment of the effectiveness of banking supervision requires a review of the legal framework, and detailed examination of the policies and practices of the institution(s) responsible for banking regulation and supervision. In line with the BCP methodology, the assessment focused on the financial services commission - financial supervisory authority (FSC-FSS). This FSAP provides introduction; information and methodology used for assessment; institutional and macroeconomic setting and market structure - overview; preconditions for effective banking supervision; summary compliance with the Basel core principles; and detailed assessment.